Comparative evaluation of sequencing technologies and primer sets for mouse gut microbiota profiling - Strokach, Aleksandra; Zoruk, Polina; Boldyreva, Daria; Morozov, Maxim; Olekhnovich, Evgenii; Veselovsky, Vladimir; Babenko, Vladislav; Selezneva, Oksana; Zakharevich, Natalia; Larin, Andrey; Koldman, Severina; Koldman, Vail; et al. (Frontiers in Microbiology, 2025)
BackgroundAdvancements in sequencing technologies, such as Illumina and Oxford Nanopore Technologies (ONT), have significantly improved microbiome research. However, variations in sequencing platforms, primer selection, and DNA quality may influence microbial diversity assessments, particularly in studies of gut microbiota. This study systematically evaluates these factors in mouse gut microbiota analysis, comparing 16S rRNA gene sequencing and metagenome sequencing (MS) across both platforms.ResultsOur findings highlight the critical influence of primer selection on 16S rRNA sequencing results, with certain primer combinations detecting unique taxa that others miss. Despite these variations in taxonomic resolution, all tested primer sets consistently revealed significant differences between experimental groups, indicating that key microbial shifts induced by bacterial cultures remain detectable regardless of primer choice. A comparative analysis of Illumina and ONT 16S rRNA sequencing revealed notable differences in microbial diversity profiling, with ONT capturing a broader range of taxa. In contrast, MS on both platforms showed a high degree of correlation, indicating that ONT sequencing errors have minimal impact on taxonomic diversity estimations. Furthermore, the type of extracted DNA (high molecular weight vs. standard DNA) had little on microbial diversity outcomes, underscoring the robustness of these sequencing technologies.ConclusionThese results highlight the advantages and limitations of different sequencing strategies in microbiota research. While 16S rRNA sequencing remains a cost-effective tool for assessing bacterial diversity, MS provides superior taxonomic resolution and more precise species identification. Our study advocates for a hybrid approach that combines multiple sequencing technologies to achieve a more comprehensive and accurate representation of microbial communities.